Lexical Hedges Inn “To All Thee Boys I’ve Loved Before” Movie - I Gusti Ayu Vinai Widiadnya Putri; Ni Made Verayanti Utami; Kendran, Ni Kadek Kendran Damayanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study aims at identifying the variety kinds of lexical1 hedges1 employed in the movie script and to determine their purpose. The data for this study were gathered from the 2018 film